Profile of poisoning cases treated in a teaching hospital of Northeast India with special reference to Poison severity score: A cross-sectional study - Anamika Das; Anupam Datta; Anamika Nath; Anirban Bhowmik (Journal of Family Medicine and Primary Care, 2022)
Background: Poisoning has been one of the greatest medical emergencies from the dawn of human civilization, posing threat to mankind. Tripura being a seven sister state of Northeast India have a unique topography, diverse ethnic groups, cross-cultural food habits, agriculture, and a horticulture-based economy that draws some distinctive type of poisoning threats compared to the rest of the Indian subcontinent. The present study was carried out to find out the epidemiological factors, toxicological profiles, and clinical outcomes of patients after consumption of poison. Methods: A cross-sectional study on 212 patients with a complaint of poisoning was conducted in a teaching hospital in Tripura, India, for 2 years, and the data were analyzed by using SPSS-15 (Statistical Package for the Social Sciences) software. Results: Out of 212 participants, males from lower socioeconomic status, farmers by occupation, and belonging to the age group of 21–30 years predominated other categories. Organophosphorus compounds were majorly ingested (38.7%). Suicide was the most common manner of poisoning (62.73%). The majority of the patients (75%) died during treatment, 39.15% of patients died in the initial 24 hours and 43.87% of the patients had severe life-threatening symptoms [grade 3 of poison severity score (PSS)] during the first 72 hours of hospital admission. A Spearman rho value of −0.740 and a P value <0.001 were found while establishing a relationship between survival time and PSS. Conclusion: Poisoning by any agents and means produces adverse effects on the human body which further influences the clinical outcome. Therefore, proper knowledge and attention regarding its clinico-toxico-epidemiological profile, accurate and timely diagnosis, and satisfactory management and prevention strategies are necessary.